2021
DOI: 10.1093/ageing/afab133
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio predicts delirium after stroke

Abstract: Background Delirium is an underdiagnosed and possibly preventable complication in acute stroke and is linked to poor outcome. Neutrophil-to-lymphocyte ratio (NLR), a marker of systemic inflammation, is also associated with poor outcome after acute ischemic stroke. Aim To determine whether NLR is a predictor of post-stroke delirium (PSD). Methods We reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…For those who were not assessed by neurologists, the patient was included in the POD group when two or more evaluators reached consensus on the diagnosis of delirium. Referring to the study by Guldolf K, et al [ 15 ], Table 1 shows the abstract symptoms and reported comments related to the specific DSM-5 criteria. Patients diagnosed with POD (cases) were matched 1:1 with patients without POD (controls) on the basis of age (± one year), sex, and anesthesia type.…”
Section: Methodsmentioning
confidence: 99%
“…For those who were not assessed by neurologists, the patient was included in the POD group when two or more evaluators reached consensus on the diagnosis of delirium. Referring to the study by Guldolf K, et al [ 15 ], Table 1 shows the abstract symptoms and reported comments related to the specific DSM-5 criteria. Patients diagnosed with POD (cases) were matched 1:1 with patients without POD (controls) on the basis of age (± one year), sex, and anesthesia type.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Jiang et al [ 26 ] indicates AFR as an independent risk factor for POD in elderly patients after total joint arthroplasty. In addition, a recent retrospective study suggests that NLR is an independent predictor of poststroke delirium among patients with acute ischemic stroke [ 16 ]. AFR is a novel indicator reflecting inflammation and nutrition status [ 27 ], while NLR is reliably reflecting inflammation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 When I 2 was <30% inconsistency considered as not serious limitation, >50 considered as serious, and more than 75% considered as very serious limitation. 5 Serious limitations when there was fewer than 4000 participants for each outcome and very serious limitations when there was fewer than 300 participants for each outcome. 6 Funnel plot revealed no asymmetry; neither test of publication bias approached P < 0:10.…”
Section: Within Hospitalizationmentioning
confidence: 99%
“…Kakhki and colleagues similarly linked a high NLR to poor poststroke outcomes [ 4 ]. There is a growing body of evidence to support the utility of the NLR as a predictive biomarker for the development of several poststroke complications, including infection, delirium, depression, hemorrhagic transformation, and early neurological deterioration [ 5 , 6 ]. Of these, infection is both the most common poststroke complication and the best predictor of mortality in stroke patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%